Effects of hydroxycinnamic acid esters on sweetpotato weevil feeding and oviposition and interactions with Bacillus thuringiensis proteins - Anyanga, M.O.; Farman, D.I.; Ssemakula, G.N.; Mwanga, Robert O.M.; Stevenson, P.C. (Springer, 2020)
Sweetpotato weevil (SPW) pest management is challenging because the pest target is sub-terranean, so the application of pesticides is impractical and usually inefective. Host plant resistance and the genetic transformation of sweetpotatoes to produce entomotoxic Bt proteins ofer potential for environmentally benign pest control. Resistance can be conferred by naturally occurring hydroxycinnamic acids which protect against oviposition by adults, but these compounds are restricted to the root surface so do not protect against the cortex bound larvae where the greatest damage occurs. Resistance could be enhanced if combined with expression of Bt proteins in transformed plants, but interactions between hydroxycinnamic acids and Bt proteins remain unknown. Here the bioactivity of Cry7Aa1 protein and hydroxycinnamic acid esters was evaluated individually and in combination against SPW larvae and mortality determined. Low and high concentrations of hydroxycinnamic acid esters alone caused signifcantly higher mortality of both weevil species in all experiments compared to the control. SPW larval mortality was greater when tested as a combination of hydroxycinnamic acid esters and Bt protein, but this efect was additive not synergistic. Although we report no evidence of antagonistic interactions, the antifeedant efects of the plant compounds conferring host plant resistance could have reduced consumption of the Bt protein in our assays leading to a lower efcacy when combined. Further work is required to determine whether the toxic efects of Bt proteins function alongside host plant resistance in sweetpotato under feld conditions.